The Cholesterol-Binding Sequence in Monomeric C-Reactive Protein Binds to the SARS-CoV-2 Spike Receptor-Binding Domain and Blocks Interaction With Angiotensin-Converting Enzyme 2 - Li, Hai-yun; Gao, Ning; Liu, Cheng-yang; Liu, Xiao-ling; Wu, Feng; Dai, Nini; Han, Jing; Li, Qiu-yu (Frontiers in Immunology, 2022)
The receptor-binding domain (RBD) of the spike protein of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) binds to the human angiotensin-converting enzyme 2 (ACE2) receptor, which is a prerequisite for the virus to enter the cell. C-reactive protein (CRP) is an important marker of inflammation and putative soluble pattern recognition receptor. Clinical elevation of CRP levels in patients with COVID-19 is one of the characteristics of the disease; however, whether CRP is involved in COVID-19 pathogenesis is unknown. Here, we report that monomeric CRP can bind to the SARS-CoV-2 spike RBD and competitively inhibit its binding to ACE2. Furthermore, truncated mutant peptide competition assays and surface plasmon resonance binding experiments showed that the cholesterol-binding sequence (CBS, amino acids 35-47) in monomeric CRP was critical for mediating the binding of mCRP to spike RBD. In a cell model of spike RBD and ACE2 interaction, the CBS motif effectively reduced the binding of spike RBD to ACE2 overexpressed on the cell surface. Thus, this study highlights the pattern recognition function of mCRP in innate immunity and provides a preliminary theoretical basis for the development of the CBS motif in mCRP into a functional peptide with both diagnostic significance and potential therapeutic capabilities.